toner

The toner composition with amorphous and crystalline polyester resins, along with hydrocarbon wax, addresses separation and gloss uniformity issues in high-speed printing by optimizing peak temperature and calorific value relationships, resulting in stable and high-quality image output.

JP7604121B2Active Publication Date: 2024-12-23CANON KK
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
JP2020103521
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-06-16
Publication Date
2024-12-23
Estimated Expiration
2040-06-16

AI Technical Summary

Technical Problem

Existing toners used in high-speed printing face issues with poor separation properties and uneven image gloss due to the difference in solidification temperatures between crystalline resins and release agents, leading to rough image surfaces and non-uniform gloss during high-speed printing.

Method used

A toner composition comprising amorphous polyester resin, crystalline polyester resin, and hydrocarbon wax, where the peak temperatures and calorific values of the wax and crystalline polyester resin satisfy specific relationships (T2w-T2c ≦ 15 and 0.8 ≦ H2w/H2c ≦ 8.0) to ensure effective separation and uniform image gloss.

Benefits of technology

The toner achieves good separation properties and excellent image gloss uniformity during high-speed printing, enabling stable output of high-quality images with improved smoothness and uniformity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007604121000001
    Figure 0007604121000001
  • Figure 0007604121000002
    Figure 0007604121000002
  • Figure 0007604121000003
    Figure 0007604121000003
Patent Text Reader

Abstract

To provide a toner that has satisfactory separability and excellent image gloss uniformity even in high-speed printing.SOLUTION: A toner includes toner particles containing an amorphous polyester resin, a crystalline polyester resin, and hydrocarbon wax. In differential scanning calorimetry (DSC), the toner is measured in I: a step of heating the toner from 20°C to 180°C at a rate of temperature increase of 10°C / min, and II: a step of cooling the toner to 20°C at a rate of temperature decrease of 10°C / min after the step I, and when the peak temperature (°C) of a peak derived from the wax measured in the step II is T2w, the calorific value (J / g) of the peak is H2w, the peak temperature (°C) derived from the crystalline polyester resin is T2c, and the calorific value (J / g) of the peak is H2c, the following relationships are satisfied. 8≤T2w-T2c; 0.8≤H2w / H2c≤8.0.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a toner used in image forming methods such as electrophotography, electrostatic recording, electrostatic printing, and toner jet methods. [Background technology]

[0002] In recent years, as full-color electrophotographic copiers have become more widespread, there is an ever-increasing demand for faster printing and energy conservation. To accommodate high-speed printing, technology is being considered that can fix toner at lower temperatures to improve productivity in the fixing process. Furthermore, in the commercial printing field, where the printed matter itself is the product, there is a stronger demand than ever before for not only productivity but also higher image quality and more stable images. In order to achieve both low-temperature fixing ability and image durability, a toner using a crystalline resin has been proposed (Patent Document 1). The above problem is solved by using a crystalline resin having a specific endothermic / exothermic peak. However, due to the difference in solidification temperature between the crystalline resin and the release agent when cooling the image, the release effect becomes insufficient, especially during high-speed printing, and the fixed image surface becomes rough, which can cause the image gloss to become non-uniform. Therefore, there is a demand for a toner that has good separation properties and excellent image gloss uniformity even during high-speed printing. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2007-86502 A Summary of the Invention [Problem to be solved by the invention]

[0004] An object of the present invention is to provide a toner which overcomes the above problems, specifically, to provide a toner which has good separation properties and excellent image gloss uniformity even during high speed printing. [Means for solving the problem]

[0005] The present invention provides a toner comprising toner particles containing an amorphous polyester resin, a crystalline polyester resin, and a hydrocarbon wax, the crystalline polyester resin is a condensation polymer of 1,12-dodecanediol and sebacic acid; The toner exhibited the following properties when measured by differential scanning calorimetry (DSC): I: Step of heating from 20°C to 180°C at a rate of 10°C / min II: After step I, a step of cooling to 20°C at a rate of 10°C / min When the measurement is performed in accordance with the above method, the toner satisfies the following relationship, where T2w is the peak temperature (°C) of the peak derived from the wax observed in step II, H2w is the calorific value (J / g), T2c is the peak temperature (°C) derived from the crystalline polyester resin, and H2c is the calorific value (J / g). 9≦T2w-T2c≦15 2.1 ≦H2w / H2c≦ 3.8 Effect of the Invention

[0006] According to the present invention, it is possible to provide a toner that has good separation properties and excellent uniformity in image gloss even during high-speed printing. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0007] In the present invention, the expressions "xx or more and xx or less" and "xx to xx" expressing a numerical range mean a numerical range including the lower and upper limit endpoints, unless otherwise specified.

[0008] Hereinafter, an embodiment of the present invention will be described in detail.

[0009] The toner of the present invention is a toner comprising toner particles containing an amorphous polyester resin, a crystalline polyester resin, and a hydrocarbon wax, and the toner has a characteristic that, when measured by differential scanning calorimetry (DSC), I: Step of heating from 20°C to 180°C at a rate of 10°C / min II: After step I, a step of cooling to 20°C at a rate of 10°C / min When the measurement is performed in the above manner, the peak temperature (°C) of the peak derived from the wax observed in step II is defined as T2w, the calorific value (J / g) is defined as H2w, the peak temperature (°C) derived from the crystalline polyester resin is defined as T2c, and the calorific value (J / g) is defined as H2c, and the following relationship is satisfied. 8≦T2w-T2c 0.8≦H2w / H2c≦8.0

[0010] The toner of the present invention has excellent separation properties and uniformity of image gloss even during high-speed printing, and therefore can stably output high-quality images.

[0011] The present inventors speculate as follows about the reason why the above problem has been solved.

[0012] In order to obtain good separation even during high-speed printing, it is necessary that the image surface during fixation and separation has sufficient releasability between the fixing member. For this purpose, it is important that a component having a releasing effect when melted is present on the image surface. In general, a component having a releasing effect that has crystallinity and low viscosity in a molten state is effective as a release agent.

[0013] The toner of the present invention contains a hydrocarbon wax and a crystalline polyester resin. Both of these components can be present on the image surface when melted. When multiple different materials are melted at the same time and are not completely compatible with each other and exist partially or entirely separated, a viscosity difference occurs due to the difference in materials, forming an interface. In addition, since a material with a lower viscosity and higher hydrophobicity precipitates on the image surface, a layered state is formed in which the release agent is present on the surface in the molten state and the crystalline polyester is in the lower layer. As a result, the interface is likely to become the starting point of the separation interface. Since the toner of the present invention contains a wax and a crystalline polyester resin with different viscosities, it is presumed that the toner has excellent separation properties when melted for the above reasons.

[0014] However, simply having multiple release agents leaves a problem in terms of image gloss uniformity. The image gloss of a printed matter is affected by the smoothness of the image surface, and if the smoothness varies, the image gloss is likely to become non-uniform. The smoothness of an image is mainly determined by the "separability" in the fixing process and the "solidification" when the image is cooled and the molten toner solidifies. The toner of the present invention has excellent separability because it has multiple release agents as described above. Furthermore, it has been found that the toner of the present invention maintains the smoothness of the image surface and has excellent gloss uniformity by setting the solidification points of the hydrocarbon wax and the crystalline polyester resin within a specific range. When the toner of the present invention is cooled from a molten state and solidifies, the wax solidifies first, and then the crystalline polyester resin solidifies. The crystalline polyester resin fills the gaps that are generated when the wax solidifies while still in a molten state, and then solidifies, thereby increasing the smoothness of the image surface.

[0015] It is believed that for the above reasons, the toner of the present invention is able to achieve both good separation properties and uniformity in image gloss.

[0016] It is important that the toner of the present invention has a releasing agent, a hydrocarbon wax, and a crystalline polyester resin, which are separated from each other when melted in the fixing step. This can be achieved by having a peak derived from the wax and a peak derived from the crystalline polyester in the process of cooling after heating in differential scanning calorimetry (DSC). If the crystalline polyester resin or wax is compatible with the amorphous polyester, or if the wax is compatible with the crystalline polyester resin, no peak is observed during cooling in DSC, and the effect of the present invention is not achieved. In order to have a peak derived from the wax and a peak derived from the crystalline polyester, respectively, this can be achieved by appropriately selecting the types and amounts of the amorphous polyester, crystalline polyester, and hydrocarbon wax, as described below.

[0017] In the present invention, the relationship between the peak temperature (°C) T2w of the peak derived from the wax and the peak temperature (°C) T2c derived from the crystalline polyester resin is 8≦T2w-T2c, preferably 9≦T2w-T2c≦20, and more preferably 9≦T2w-T2c≦15.

[0018] If T2w-T2c<8, the freezing temperatures of the wax and the crystalline polyester resin become close to each other, and the crystalline polyester resin cannot sufficiently fill the gaps that are generated when the wax solidifies, resulting in reduced image smoothness and possibly uneven image gloss.

[0019] In the present invention, the relationship between the peak calorific value (J / g) H2w derived from the wax and the peak calorific value (J / g) H2c derived from the crystalline polyester resin is 0.8≦H2w / H2c≦8.0, preferably 1.0≦H2w / H2c≦6.0, and more preferably 1.2≦H2w / H2c≦4.0.

[0020] If H2w / H2c is greater than 0.8, the ratio of wax with a lower viscosity in a molten state becomes relatively small, which may result in poor separation. Also, when the wax solidifies, there may be too many gaps, which may result in poor image smoothness.

[0021] If H2w / H2c>8.0, the wax content will be too high, making the upper layer (the outermost surface of the image) too thick, or the lower layer (crystalline polyester resin) too thin, reducing the interface area, which may reduce the effect of the interface in improving separation.

[0022] The value of T2w-T2c can be controlled by changing the type of wax, crystalline polyester resin, or amorphous polyester resin used.

[0023] The value of H2w / H2c can be controlled by the type and amount of the wax or crystalline polyester resin used, the type of amorphous polyester resin, and the like.

[0024] In addition, when wax or crystalline polyester resin is measured by DSC alone, the peak temperature and amount of heat generated during cooling do not always match. This is because toner is a compound with other materials and is affected by the presence of surrounding materials and the degree of compatibility with them. For example, when the amorphous polyester resin and the crystalline polyester resin are completely compatible in the toner, an exothermic peak is observed during cooling in the DSC of the crystalline polyester resin alone, whereas no exothermic peak is observed during cooling in the DSC of the toner.

[0025] In the present invention, a preferred toner configuration will be described in detail below.

[0026] [Binding resin] The toner of the present invention contains an amorphous polyester resin as a binder resin.

[0027] The amorphous polyester resin is preferable from the viewpoint of achieving both low-temperature fixability and electrostatic chargeability. From the viewpoint of density stability after a long-term test, the content of the amorphous polyester resin in the total binder resin is 50% by mass or more and 100% by mass or less, and preferably 70% by mass or more and 100% by mass or less.

[0028] Monomers used in the synthesis of amorphous polyester resin include polyhydric alcohols (divalent or trivalent or higher alcohols), polyvalent carboxylic acids (divalent or trivalent or higher carboxylic acids), their acid anhydrides or their lower alkyl esters. When preparing a branched polymer, it is effective to partially crosslink the binder resin molecule, and for this purpose, it is preferable to use a polyfunctional compound having a valence of three or more. Therefore, it is preferable to include a trivalent or higher carboxylic acid, its acid anhydride or its lower alkyl ester, and / or a trivalent or higher alcohol as the raw material monomer.

[0029] As the polyhydric alcohol monomer, the following polyhydric alcohol monomers can be used.

[0030] Examples of dihydric alcohol components include the following: ethylene glycol, propylene glycol, 1,3-butanediol, 1,4-butanediol, 2,3-butanediol, diethylene glycol, triethylene glycol, 1,5-pentanediol, 1,6-hexanediol, neopentyl glycol, 2-ethyl-1,3-hexanediol, hydrogenated bisphenol A, and bisphenol represented by formula (A) and its derivatives.

[0031] [ka] (In the formula, R is an ethylene or propylene group, x and y are each an integer of 0 or more, and the average value of x+y is 0 or more and 10 or less.)

[0032] Diols represented by formula (B);

[0033] [ka]

[0034] Examples of trihydric or higher alcohol components include sorbitol, 1,2,3,6-hexanetetrol, 1,4-sorbitan, pentaerythritol, dipentaerythritol, tripentaerythritol, 1,2,4-butanetriol, 1,2,5-pentanetriol, glycerol, 2-methylpropanetriol, 2-methyl-1,2,4-butanetriol, trimethylolethane, trimethylolpropane, and 1,3,5-trihydroxymethylbenzene. Among these, glycerol, trimethylolpropane, and pentaerythritol are preferably used. These dihydric alcohols and trihydric or higher alcohols can be used alone or in combination.

[0035] As the polybasic carboxylic acid monomer, the following polybasic carboxylic acid monomers can be used.

[0036] Examples of divalent carboxylic acid components include maleic acid, fumaric acid, citraconic acid, itaconic acid, glutaconic acid, phthalic acid, isophthalic acid, terephthalic acid, succinic acid, adipic acid, sebacic acid, azelaic acid, malonic acid, n-dodecenylsuccinic acid, isododecenylsuccinic acid, n-dodecylsuccinic acid, isododecylsuccinic acid, n-octenylsuccinic acid, n-octylsuccinic acid, isooctylsuccinic acid, isooctylsuccinic acid, anhydrides of these acids, and lower alkyl esters thereof. Of these, maleic acid, fumaric acid, terephthalic acid, and n-dodecenylsuccinic acid are preferably used.

[0037] Examples of trivalent or higher carboxylic acids, their anhydrides or their lower alkyl esters include 1,2,4-benzenetricarboxylic acid, 2,5,7-naphthalenetricarboxylic acid, 1,2,4-naphthalenetricarboxylic acid, 1,2,4-butanetricarboxylic acid, 1,2,5-hexanetricarboxylic acid, 1,3-dicarboxyl-2-methyl-2-methylenecarboxypropane, 1,2,4-cyclohexanetricarboxylic acid, tetra(methylenecarboxyl)methane, 1,2,7,8-octanetetracarboxylic acid, pyromellitic acid, empol trimer acid, their anhydrides or their lower alkyl esters. Among these, 1,2,4-benzenetricarboxylic acid, i.e., trimellitic acid or its derivatives, is particularly preferred because it is inexpensive and easy to control the reaction. These divalent carboxylic acids and trivalent or higher carboxylic acids can be used alone or in combination.

[0038] The method for synthesizing the polyester resin is not particularly limited, and a known method can be used. For example, the above-mentioned alcohol monomer and carboxylic acid monomer are simultaneously charged, and polymerized through an esterification reaction or an ester exchange reaction and a condensation reaction to produce a polyester resin. The polymerization temperature is not particularly limited, but is preferably in the range of 180°C to 290°C. For the polymerization of the polyester unit, for example, a polymerization catalyst such as a titanium-based catalyst, a tin-based catalyst, zinc acetate, antimony trioxide, or germanium dioxide can be used. In particular, the amorphous polyester resin of the present invention is more preferably a polyester resin polymerized using a tin-based catalyst.

[0039] The main component of the alcohol component constituting the amorphous polyester resin used in the toner of the present invention is preferably an aromatic diol, and the aromatic diol is preferably contained at a ratio of 80 mol% to 100 mol%, and more preferably at a ratio of 90 mol% to 100 mol%. Furthermore, the aromatic diol is preferably a bisphenol represented by the above formula (A) and a derivative thereof, and more preferably contains an alcohol component derived from an ethylene oxide adduct at 30 mol% or more, and more preferably at 50 mol% or more. With the above-mentioned constitution, the state of existence of the hydrocarbon wax and the crystalline polyester resin on the image surface when the toner is melted can be easily controlled to the above-mentioned specific range.

[0040] The main component of the acid component constituting the amorphous polyester resin used in the toner of the present invention is preferably an aromatic divalent or trivalent carboxylic acid, and the aromatic divalent or trivalent carboxylic acid is preferably contained in an amount of 80 mol % or more and 100 mol % or less, more preferably 90 mol % or more and 100 mol % or less.

[0041] In addition, the ratio of aliphatic dicarboxylic acids among the acid components constituting the amorphous polyester resin used in the toner of the present invention is preferably 10 mol % or less, from the viewpoint of easily controlling the H2c and T2c values ​​of the crystalline polyester resin within the range of the present invention, and more preferably 5 mol % or less.

[0042] These binder resins may be used alone or in combination with a plurality of different resins. In particular, it is preferable to combine two or more resins having different softening points, since this allows the viscoelastic properties of the toner to be adjusted and makes it relatively easy to achieve both low-temperature fixability and hot offset resistance.

[0043] The softening point of these binder resins is preferably 70° C. or higher and 180° C. or lower, more preferably 80° C. or higher and 160° C. or lower, from the viewpoint of achieving both low-temperature fixability and hot offset resistance.

[0044] [Crystalline polyester resin] The toner of the present invention contains a crystalline polyester resin.

[0045] The content of the crystalline polyester resin is preferably 0.5 parts by mass or more and 15.0 parts by mass or less, and more preferably 1.0 parts by mass or more and 10.0 parts by mass or less, relative to 100.0 parts by mass of the binder resin.

[0046] When the content of the crystalline polyester resin is within the above range, the toner has good separation property and excellent uniformity of image gloss. When the content of the crystalline polyester resin is less than 0.5 parts by mass, the crystalline polyester resin cannot sufficiently fill the gaps generated when the wax solidifies, resulting in low image smoothness and non-uniform image gloss. When the content of the crystalline polyester resin is more than 15.0 parts by mass, the crystalline polyester resin tends to be difficult to finely disperse in the toner particles, which may result in a decrease in charging stability.

[0047] In the present invention, a crystalline resin is a resin in which an endothermic peak is observed in differential scanning calorimetry (DSC).

[0048] The crystalline polyester resin can be obtained by the reaction of a divalent or higher polyvalent carboxylic acid and a diol. Among them, a resin obtained by polycondensation of an aliphatic diol and an aliphatic dicarboxylic acid is preferred because it has a high degree of crystallinity and is easily interactive with copper phthalocyanine. In the present invention, the crystalline polyester resin may be used alone or in combination of multiple types.

[0049] In the present invention, the crystalline polyester resin is preferably a resin obtained by condensation polymerization of an alcohol component containing at least one compound selected from the group consisting of aliphatic diols having from 2 to 22 carbon atoms and derivatives thereof, and a carboxylic acid component containing at least one compound selected from the group consisting of aliphatic dicarboxylic acids having from 2 to 22 carbon atoms and derivatives thereof.

[0050] Among these, from the viewpoint of good separability and uniformity of image gloss, it is more preferable that the crystalline polyester resin is a crystalline polyester resin obtained by condensation polymerization of an alcohol component containing at least one compound selected from the group consisting of aliphatic diols having 6 to 14 carbon atoms and derivatives thereof, and a carboxylic acid component containing at least one compound selected from the group consisting of aliphatic dicarboxylic acids having 6 to 14 carbon atoms and derivatives thereof.

[0051] The aliphatic diol having 2 to 22 carbon atoms (preferably having 6 to 14 carbon atoms) is not particularly limited, but is optimal from the viewpoint of improving good separability and image gloss uniformity by being a chain (preferably linear) aliphatic diol.

[0052] Examples include ethylene glycol, diethylene glycol, triethylene glycol, 1,2-propylene glycol, dipropylene glycol, 1,3-propanediol, 1,4-butanediol, 1,4-butadiene glycol, 1,5-pentanediol, neopentyl glycol, 1,6-hexanediol, 1,7-heptanediol, 1,8-octanediol, 1,9-nonanediol, 1,10-decanediol, 1,11-undecanediol, 1,12-dodecanediol, 1,13-tridecanediol, and 1,14-tetradecanediol.

[0053] Among these, preferred examples include straight-chain aliphatic α,ω-diols such as 1,6-hexanediol, 1,7-heptanediol, 1,8-octanediol, 1,9-nonanediol, 1,10-decanediol, 1,11-undecanediol, 1,12-dodecanediol, 1,13-tridecanediol, and 1,14-tetradecanediol.

[0054] In the present invention, the derivative is not particularly limited as long as it can give a similar resin structure by the above-mentioned condensation polymerization, and examples thereof include derivatives obtained by esterifying the above-mentioned diols.

[0055] In the present invention, in the alcohol component constituting the crystalline polyester resin, at least one compound selected from the group consisting of the aliphatic diols having 2 to 22 carbon atoms (preferably 6 to 14 carbon atoms) and their derivatives is preferably present in an amount of 50 mass% or more, more preferably 70 mass% or more, based on the total alcohol component.

[0056] In the present invention, polyhydric alcohols other than the above-mentioned aliphatic diols can also be used. Among the polyhydric alcohols, examples of the diols other than the above-mentioned aliphatic diols include aromatic alcohols such as polyoxyethylenated bisphenol A and polyoxypropylenated bisphenol A; 1,4-cyclohexanedimethanol, and the like.

[0057] Furthermore, examples of the polyhydric alcohols having a valence of three or more include aromatic alcohols such as 1,3,5-trihydroxymethylbenzene; and aliphatic alcohols such as pentaerythritol, dipentaerythritol, tripentaerythritol, 1,2,4-butanetriol, 1,2,5-pentanetriol, glycerin, 2-methylpropanetriol, 2-methyl-1,2,4-butanetriol, trimethylolethane, and trimethylolpropane.

[0058] Furthermore, in the present invention, monohydric alcohols may be used to the extent that they do not impair the properties of the crystalline polyester resin. Examples of the monohydric alcohols include n-butanol, isobutanol, sec-butanol, n-hexanol, n-octanol, 2-ethylhexanol, cyclohexanol, and benzyl alcohol.

[0059] On the other hand, the aliphatic dicarboxylic acid having 2 to 22 carbon atoms (preferably 6 to 14 carbon atoms) is not particularly limited, but may be a chain-like (preferably linear) aliphatic dicarboxylic acid. Examples include oxalic acid, malonic acid, succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, glutaconic acid, azelaic acid, sebacic acid, nonanedicarboxylic acid, decanedicarboxylic acid, undecanedicarboxylic acid, dodecanedicarboxylic acid, maleic acid, fumaric acid, mesaconic acid, citraconic acid, and itaconic acid. Also included are those obtained by hydrolyzing the acid anhydrides or lower alkyl esters of these acids.

[0060] In the present invention, the derivative is not particularly limited as long as it can give a similar resin structure by the above-mentioned condensation polymerization. For example, there can be mentioned acid anhydrides of the above-mentioned dicarboxylic acid components, and derivatives obtained by converting the dicarboxylic acid components into methyl esters, ethyl esters, or acid chlorides.

[0061] In the present invention, in the carboxylic acid components constituting the crystalline polyester resin, at least one compound selected from the group consisting of the aliphatic dicarboxylic acids having 2 to 22 carbon atoms (preferably 6 to 14 carbon atoms) and their derivatives preferably accounts for 50 mass % or more, and more preferably 70 mass % or more, of the total carboxylic acid components.

[0062] In the present invention, polyvalent carboxylic acids other than the above-mentioned aliphatic dicarboxylic acids can also be used. Among the polyvalent carboxylic acids, examples of divalent carboxylic acids other than the above-mentioned aliphatic dicarboxylic acids include aromatic carboxylic acids such as isophthalic acid and terephthalic acid, aliphatic carboxylic acids such as n-dodecyl succinic acid and n-dodecenyl succinic acid, and alicyclic carboxylic acids such as cyclohexane dicarboxylic acid, and also include their acid anhydrides or lower alkyl esters.

[0063] Furthermore, among other polyvalent carboxylic acids, examples of trivalent or higher polyvalent carboxylic acids include aromatic carboxylic acids such as 1,2,4-benzenetricarboxylic acid (trimellitic acid), 2,5,7-naphthalenetricarboxylic acid, 1,2,4-naphthalenetricarboxylic acid, and pyromellitic acid, and aliphatic carboxylic acids such as 1,2,4-butanetricarboxylic acid, 1,2,5-hexanetricarboxylic acid, and 1,3-dicarboxyl-2-methyl-2-methylenecarboxypropane, and also include derivatives such as acid anhydrides and lower alkyl esters of these.

[0064] Furthermore, in the present invention, a monovalent carboxylic acid may be used to the extent that it does not impair the properties of the crystalline polyester resin. Examples of the monovalent carboxylic acid include benzoic acid, naphthalene carboxylic acid, salicylic acid, 4-methylbenzoic acid, 3-methylbenzoic acid, phenoxyacetic acid, biphenyl carboxylic acid, acetic acid, propionic acid, butyric acid, and octanoic acid.

[0065] In the present invention, the crystalline polyester resin can be produced according to a conventional polyester synthesis method. For example, the crystalline polyester resin can be obtained by esterifying or transesterifying the carboxylic acid component and the alcohol component, and then condensing the mixture under reduced pressure or by introducing nitrogen gas according to a conventional method.

[0066] The above esterification or transesterification reaction can be carried out, if necessary, using a conventional esterification catalyst or transesterification catalyst such as sulfuric acid, titanium butoxide, tin 2-ethylhexanoate, dibutyltin oxide, manganese acetate, or magnesium acetate.

[0067] The condensation polymerization reaction can be carried out using a conventional polymerization catalyst, such as titanium butoxide, tin 2-ethylhexanoate, dibutyltin oxide, tin acetate, zinc acetate, tin disulfide, antimony trioxide, germanium dioxide, etc. The polymerization temperature and the amount of catalyst are not particularly limited and may be appropriately determined.

[0068] In the esterification or transesterification reaction, or polycondensation reaction, a method may be used in which all monomers are charged at once in order to increase the strength of the resulting crystalline polyester resin, or a divalent monomer is first reacted in order to reduce low molecular weight components, and then a trivalent or higher monomer is added and reacted.

[0069] In the crystalline polyester resin of the present invention, the total number of carbon atoms derived from the alcohol unit and the carbon number derived from the carboxylic acid unit is preferably from 20 to 30, and more preferably from 22 to 26. When the total number of carbon atoms is within the above range, the rate of seeping onto the image surface when the toner is melted becomes appropriate, the image smoothness is improved, and the image gloss becomes more uniform.

[0070] The weight average molecular weight Mwc of the crystalline polyester resin of the present invention preferably satisfies the relationship 3≦Mwc / Mwa when the weight average molecular weight Mwa of the amorphous polyester resin is used. If Mwc / Mwa is in this range, it is preferable because the charging stability is easily improved. More preferably, it is 4≦Mwc / Mwa. When multiple amorphous polyester resins are used, the weight average molecular weight is that of the amorphous polyester with the largest content.

[0071] [wax] The toner of the present invention contains a hydrocarbon wax.

[0072] Hydrocarbon waxes are less compatible with crystalline polyesters than general ester waxes, and a laminated structure in which the hydrocarbon wax and the crystalline polyester are melted can be formed during the fixing process, thereby achieving the effects of the present invention.

[0073] Examples of the hydrocarbon wax include hydrocarbon waxes such as low molecular weight polyethylene, low molecular weight polypropylene, alkylene copolymers, microcrystalline wax, paraffin wax, and Fischer-Tropsch wax; oxides of hydrocarbon waxes such as oxidized polyethylene wax, and block copolymers thereof.

[0074] Among these waxes, from the viewpoint of improving coloring power and electrostatic chargeability, and further from the viewpoint of being less compatible with crystalline polyester and improving separability, paraffin wax or Fischer-Tropsch wax is preferred, and Fischer-Tropsch wax is more preferred.

[0075] The toner of the present invention may contain other waxes as necessary. Waxes mainly composed of fatty acid esters such as carnauba wax; partially or completely deoxidized fatty acid esters such as deoxidized carnauba wax; and the following. Saturated straight-chain fatty acids such as palmitic acid, stearic acid, and montanic acid; unsaturated fatty acids such as brassidic acid, eleostearic acid, and valinaric acid; saturated alcohols such as stearyl alcohol, aralkyl alcohol, behenyl alcohol, carnaubyl alcohol, ceryl alcohol, and melissyl alcohol; polyhydric alcohols such as sorbitol; esters of fatty acids such as palmitic acid, stearic acid, behenic acid, and montanic acid with alcohols such as stearyl alcohol, aralkyl alcohol, behenyl alcohol, carnaubyl alcohol, ceryl alcohol, and melissyl alcohol; fatty acid amides such as linoleic acid amide, oleic acid amide, and lauric acid amide; methylene bisstearic acid amide, ethylene biscapric acid amide, ethylene bislauric acid amide, hexamethylene Saturated fatty acid bisamides such as bisstearamide; unsaturated fatty acid amides such as ethylene bisoleamide, hexamethylene bisoleamide, N,N' dioleyl adipamide, and N,N' dioleyl sebacamide; aromatic bisamides such as m-xylene bisstearamide and N,N' distearyl isophthalamide; fatty metal salts (commonly known as metal soaps) such as calcium stearate, calcium laurate, zinc stearate, and magnesium stearate; waxes grafted onto aliphatic hydrocarbon waxes using vinyl monomers such as styrene and acrylic acid; partial esters of fatty acids and polyhydric alcohols such as behenic acid monoglyceride; and methyl ester compounds having hydroxyl groups obtained by hydrogenating vegetable oils and fats.

[0076] The content of the wax is preferably 0.5 parts by mass or more and 20.0 parts by mass or less relative to 100.0 parts by mass of the binder resin. More preferably, it is 3.0 parts by mass or more and 12.0 parts by mass or less. From the viewpoint of improving the coloring power of the toner, the peak temperature of the maximum endothermic peak present in the temperature range of 30°C to 200°C in the endothermic curve during temperature rise measured by a differential scanning calorimeter (DSC) is preferably 70°C to 110°C. More preferably, it is 85°C to 100°C.

[0077] [Coloring agent] The toner particles of the toner of the present invention may contain a colorant. As the colorant, a known yellow colorant, magenta colorant, cyan colorant, or black colorant can be used.

[0078] Examples of black colorants include carbon black, and colorants toned to black using a yellow colorant, a magenta colorant, and a cyan colorant.

[0079] As the colorant, a pigment or a dye may be used alone, or a dye and a pigment may be used in combination.

[0080] The content of the colorant in the toner particles is preferably 0.1 parts by mass or more and 30.0 parts by mass or less with respect to 100.0 parts by mass of the binder resin in the toner particles.

[0081] [Magnetic material] The toner of the present invention may be a magnetic toner or a non-magnetic toner. When used as a magnetic toner, it is preferable to use magnetic iron oxide as the magnetic material contained in the toner particles. Examples of magnetic iron oxide include magnetite, maghematite, and ferrite.

[0082] The content of the magnetic material in the toner particles is preferably 25 parts by mass or more and 95 parts by mass or less, and more preferably 30 parts by mass or more and 45 parts by mass or less, relative to 100 parts by mass of the binder resin in the toner particles.

[0083] [Charge control agent] The toner particles of the toner of the present invention may contain a charge control agent. The charge control agent includes a negative charge control agent and a positive charge control agent.

[0084] Examples of negative charge control agents include metal salicylate compounds, metal naphthoate compounds, metal dicarboxylate compounds, polymeric compounds having sulfonic acid or carboxylic acid on the side chain, polymeric compounds having sulfonate or sulfonate ester on the side chain, polymeric compounds having carboxylate or carboxylate ester on the side chain, boron compounds, urea compounds, silicon compounds, and calixarenes.

[0085] When the toner particles contain a charge control agent, the charge control agent may be added internally or externally to the toner particles.

[0086] The content of the charge control agent in the toner particles is preferably 0.05 parts by mass or more and 10.0 parts by mass or less with respect to 100.0 parts by mass of the binder resin in the toner particles.

[0087] [External additives] The toner of the present invention may further contain an external additive in order to improve the fluidity of the toner and adjust the amount of triboelectric charge.

[0088] As the inorganic external additive, inorganic fine particles such as silicon oxide (silica), aluminum oxide (alumina), titanium oxide (titania), strontium titanate, calcium carbonate, etc. are preferred. The inorganic fine particles are preferably hydrophobized with a hydrophobizing agent such as a silane compound, silicone oil, or a mixture thereof.

[0089] Examples of additives other than inorganic external additives include fine particles of resin such as vinyl resin, polyester, and silicone resin.

[0090] The external additive is preferably used in an amount of 0.1 parts by mass or more and 5.0 parts by mass or less with respect to 100.0 parts by mass of the toner particles.

[0091] These inorganic fine particles and resin fine particles function as assistants for controlling the chargeability of the toner and for improving fluidity and cleaning.

[0092] [Mixing of toner particles and external additives] To mix the toner particles and the external additives, a known mixer such as a Henschel mixer, a double con mixer, a V-type mixer, a drum type mixer, a super mixer, a Nauta mixer, or a Mechano Hybrid (manufactured by Nippon Coke and Engineering Co., Ltd.) can be used.

[0093] [Career] The toner of the present invention is preferably used as a two-component developer by mixing it with a magnetic carrier, from the viewpoint of obtaining stable images over a long period of time.

[0094] As the magnetic carrier, for example, known magnetic carriers can be used, such as surface-oxidized or unoxidized iron powder, metal particles such as iron, lithium, calcium, magnesium, nickel, copper, zinc, cobalt, manganese, and rare earth elements, or alloy particles, oxide particles, and magnetic particles such as ferrite, and magnetic material-dispersed resin carriers (so-called resin carriers) containing magnetic particles and a binder resin that holds the magnetic particles in a dispersed state.

[0095] [Method of manufacturing toner particles] The toner particles of the present invention can be produced by a known method for producing toner particles, such as a melt kneading method, an emulsion aggregation method, or a dissolution suspension method.

[0096] Next, the methods for measuring the various physical properties related to the present invention will be described.

[0097] [Measurement of peak temperature and heat release rate of wax and crystalline polyester resin] The peak temperature and heat of fusion of the wax and the crystalline polyester resin are measured in accordance with ASTM D3418-82 using a differential scanning calorimeter "Q1000" (manufactured by TA Instruments). For temperature correction of the apparatus detection part, the melting points of indium and zinc are used, and for heat correction, the heat of fusion of indium is used.

[0098] Specifically, approximately 5 mg of the sample is precisely weighed, placed in an aluminum pan, and an empty aluminum pan is used as a reference. The measurement is carried out according to the following procedure. A step of heating from 20 °C to 180 °C at a heating rate of 10 °C / min (step I), followed by a step of cooling to 20 °C at a cooling rate of 10 °C / min (step II), and then a step of heating from 20 °C to 180 °C again at a heating rate of 10 °C / min (step III). Let the peak temperature (°C) of the peak derived from the wax observed in step II be T2w, the heat of fusion (J / g) be H2w, the peak temperature (°C) of the peak derived from the crystalline polyester resin be T2c, and the heat of fusion (J / g) be H2c. Also, the temperature showing the maximum endothermic peak of the DSC curve observed in step III is taken as the peak temperature of the maximum endothermic peak of the wax and the crystalline polyester resin.

[0099] As a method for determining whether the peak is derived from the wax or the crystalline polyester, for example, the following method can be mentioned. After dispersing the toner in hexane to dissolve the wax and then extracting and drying the hexane-insoluble matter, DSC measurement is performed. By comparing with the DSC profile of the toner, the disappeared peak can be determined as the peak derived from the wax.

[0100] <Measurement of the weight average molecular weight of the resin by GPC> The weight average molecular weight (Mw) of the THF-soluble fraction of the amorphous polyester resin and the crystalline polyester resin is measured by gel permeation chromatography (GPC) as follows.

[0101] First, the toner is dissolved in tetrahydrofuran (THF) at room temperature for 24 hours. The resulting solution is then filtered through a solvent-resistant membrane filter "Myshoridisc" (manufactured by Tosoh Corporation) with a pore size of 0.2 μm to obtain a sample solution. The sample solution is adjusted so that the concentration of components soluble in THF is approximately 0.8 mass%. Using this sample solution, measurements are performed under the following conditions. Equipment: HLC8120 GPC (detector: RI) (Tosoh Corporation) Column: Shodex KF-801, 802, 803, 804, 805, 806, 807 (Showa Denko) Eluent: tetrahydrofuran (THF) Flow rate: 1.0ml / min Oven temperature: 40.0℃ Sample injection volume: 0.10 mL In calculating the molecular weight of the sample, a molecular weight calibration curve prepared using standard polystyrene resins (e.g., trade names "TSK Standard Polystyrene F-850, F-450, F-288, F-128, F-80, F-40, F-20, F-10, F-4, F-2, F-1, A-5000, A-2500, A-1000, A-500" manufactured by Tosoh Corporation) is used.

[0102] [Measurement of weight average particle size (D4) of toner particles] The weight-average particle diameter (D4) of the toner particles is measured with an effective measurement channel count of 25,000 channels using a precision particle size distribution measuring device using the narrow hole electrical resistance method, "Coulter Counter Multisizer 3" (registered trademark, manufactured by Beckman Coulter, Inc.), equipped with a 100 μm aperture tube, and the accompanying dedicated software for setting measurement conditions and analyzing measurement data, "Beckman Coulter Multisizer 3 Version 3.51" (manufactured by Beckman Coulter, Inc.), and the measurement data is analyzed and calculated.

[0103] The aqueous electrolyte solution used for the measurement is prepared by dissolving special grade sodium chloride in deionized water to a concentration of approximately 1% by mass, for example, "ISOTON II" (manufactured by Beckman Coulter).

[0104] Before carrying out the measurements and analyses, the dedicated software is set up as follows.

[0105] In the "Change Standard Measurement Method (SOM) screen" of the dedicated software, set the total count number in the control mode to 50,000 particles, the number of measurements to 1, and the Kd value to the value obtained using "Standard Particle 10.0 μm" (Beckman Coulter). Press the threshold / noise level measurement button to automatically set the threshold and noise level. In addition, set the current to 1600 μA, the gain to 2, the electrolyte to ISOTON II, and check the aperture tube flush after measurement.

[0106] In the "Pulse to particle size conversion setting screen" of the dedicated software, set the bin interval to logarithmic particle size, the particle size bin to 256 particle size bins, and the particle size range to 2 μm to 60 μm.

[0107] The specific measurement methods are as follows (1) to (7). (1) Pour about 200 ml of the electrolyte solution into a 250 ml round-bottom glass beaker made exclusively for the Multisizer 3, set it on the sample stand, and stir the stirrer rod counterclockwise at 24 revolutions per second. Then, use the "aperture flush" function of the analysis software to remove dirt and air bubbles from inside the aperture tube. (2) Approximately 30 ml of the aqueous electrolyte solution is placed in a 100 ml flat-bottom glass beaker, and approximately 0.3 ml of a solution prepared by diluting "Contaminon N" (a 10% aqueous solution of a neutral detergent for cleaning precision measuring instruments with a pH of 7 consisting of a nonionic surfactant, anionic surfactant, and organic builder, manufactured by Wako Pure Chemical Industries, Ltd.) three times by mass with deionized water is added as a dispersant. (3) A specified amount of deionized water is placed in the water tank of an ultrasonic disperser "Ultrasonic Dispension System Tetora150" (manufactured by Nikkaki Bios Co., Ltd.) that has two oscillators with an oscillation frequency of 50 kHz built in with a phase shift of 180 degrees and an electrical output of 120 W, and approximately 2 ml of the Conaminon N is added to this water tank. (4) The beaker (2) is set in the beaker fixing hole of the ultrasonic disperser, and the ultrasonic disperser is operated. Then, the height position of the beaker is adjusted so that the resonance state of the liquid surface of the electrolyte solution in the beaker is maximized. (5) While the electrolyte solution in the beaker in (4) is irradiated with ultrasonic waves, about 10 mg of toner is added little by little to the electrolyte solution and dispersed. Then, ultrasonic dispersion treatment is continued for another 60 seconds. Note that during ultrasonic dispersion, the water temperature in the water tank is appropriately adjusted to be 10°C or higher and 40°C or lower. (6) In the round-bottom beaker (1) placed in the sample stand, the electrolyte solution (5) in which the toner is dispersed is dropped using a pipette to adjust the measurement concentration to about 5%. Then, measurements are continued until the number of particles measured reaches 50,000. (7) The measurement data is analyzed using the dedicated software that comes with the device, and the weight-average particle size (D4) is calculated. Note that when the dedicated software is set to Graph / Volume%, the "Average diameter" on the Analysis / Volume Statistics (Arithmetic Mean) screen is the weight-average particle size (D4). EXAMPLES

[0108] The present invention will be described below with reference to Production Examples and Examples. 3 ~12 is a reference example.

[0109] <Examples of binder resin production> <Production Example of Amorphous Polyester Resin A1> Polyoxypropylene(2.2)-2,2-bis(4-hydroxyphenyl)propane: 100.0 mol% Terephthalic acid: 80.0 mol% based on the total number of moles of polycarboxylic acids Trimellitic anhydride: 20.0 mol% based on the total number of moles of polycarboxylic acids The monomer material was put into a reaction vessel equipped with a cooling pipe, a stirrer, a nitrogen inlet pipe, and a thermocouple. Then, 1.5 parts by mass of tin 2-ethylhexanoate was added as a catalyst (esterification catalyst) to 100 parts by mass of the total amount of the monomer material. Next, the inside of the reaction vessel was replaced with nitrogen gas, and the temperature was gradually raised while stirring, and the reaction was carried out for 2 hours while stirring at a temperature of 200°C.

[0110] Furthermore, the pressure in the reaction vessel was reduced to 8.3 kPa and maintained for 1 hour, after which it was cooled to 180 and reacted as is. After confirming that the softening point, measured in accordance with ASTM D36-86, reached 122°C, the temperature was reduced to stop the reaction.

[0111] The obtained amorphous polyester resin 1 had a softening point (Tm) of 112°C, a glass transition temperature (Tg) of 63°C, and a weight average molecular weight (Mw) of 5,200.

[0112] <Production Example of Amorphous Polyester Resin A2> Amorphous polyester resin 2 was produced in the same manner as for amorphous polyester resin 1, except that polyoxypropylene(2.2)-2,2-bis(4-hydroxyphenyl)propane was used instead of polyoxyethylene(2.2)-2,2-bis(4-hydroxyphenyl)propane. The softening point (Tm) of the obtained amorphous polyester resin 2 was 110°C, the glass transition temperature (Tg) was 60°C, and the weight average molecular weight (Mw) was 5,400.

[0113] <Production Example of Crystalline Polyester Resin B1> 1,12-Dodecanediol 100.0mol% Sebacic acid 100.0mol% The monomers and 0.2% by mass of dibutyltin oxide based on the total amount of the monomers were placed in a 10L four-neck flask equipped with a nitrogen inlet tube, a dehydration tube, a stirrer, and a thermocouple, and reacted at 180°C for 4 hours, then heated to 200°C at a rate of 10°C / hour, held at 200°C for 8 hours, and reacted at 8.3kPa for 1 hour to obtain crystalline polyester resin B1 (B-1). The endothermic peak temperature of the obtained crystalline polyester resin B1 in differential scanning calorimetry (DSC) was 82°C. The weight average molecular weight Mw was 22000.

[0114] <Production Examples of Crystalline Polyester Resins B2 to B5> Crystalline polyester resins B2 to B5 were obtained in the same manner as in the production example of crystalline polyester B1, except that the types of alcohol component and acid component were changed as shown in Table 1. The physical properties of these crystalline polyester resins are shown in Table 1.

[0115] <Production Example of Crystalline Polyester Resin B6> 1,10-Dodecanediol 100.0mol% Adipic acid 100.0mol% The monomers and 2.0% by mass of dibutyltin oxide based on the total amount of the monomers were placed in a 10L four-neck flask equipped with a nitrogen inlet tube, a dehydration tube, a stirrer, and a thermocouple, and reacted at 180°C for 1 hour, then heated to 200°C at a rate of 10°C / hour, held at 200°C for 2 hours, and reacted at 8.3kPa for 1 hour to obtain crystalline polyester resin B6 (B-6). The endothermic peak temperature in differential scanning calorimetry (DSC) of the obtained crystalline polyester resin B6 was 68°C. The weight average molecular weight Mw was 6000.

[0116] [Table 1]

[0117] [Example 1] <Toner 1 Manufacturing Example> Amorphous polyester resin A1: 40.0 parts by weight Amorphous polyester resin A2: 60.0 parts by weight Crystalline polyester resin B1: 3.0 parts by weight 3,5-di-t-butylsalicylic acid aluminum compound: 0.5 parts by mass Fischer-Tropsch wax (maximum endothermic peak temperature: 90°C): 5.0 parts by mass CI Pigment Blue 15: 6.0 parts by weight The above raw materials were mixed in a Henschel mixer (product name: FM75J type, manufactured by Mitsui Miike Chemical Engineering Co., Ltd.) at a rotation speed of 20 s. -1 After mixing under conditions of 1000 rpm and a rotation time of 5 minutes, the mixture was kneaded in a twin-screw kneader (product name: PCM-30, manufactured by Ikegai Corporation) set at a temperature of 125°C. The kneaded mixture was cooled and coarsely crushed to 1 mm or less using a hammer mill to obtain a coarsely crushed product. The coarsely crushed product was finely crushed using a mechanical crusher (product name: T-250, manufactured by Turbo Kogyo Co., Ltd.). Further, classification was performed using a rotary classifier (product name: 200TSP, manufactured by Hosokawa Micron Corporation) to obtain toner particles 1. The operating conditions of the rotary classifier were a classification rotor rotation speed of 50.0 s -1 It was decided.

[0118] The resulting toner particles 1 had a weight average particle size (D4) of 6.2 μm.

[0119] To 100.0 parts by mass of the obtained toner particles 1, 1.0 part by mass of hydrophobic silica fine particles having a primary average particle size of 15 nm and surface-treated with 20.0% by mass of hexamethyldisilazane, and 1.0 part by mass of strontium titanate particles having a primary average particle size of 35 nm were added, and the mixture was mixed in a Henschel mixer (FM75J type, manufactured by Mitsui Miike Chemical Engineering Co., Ltd.) at a rotation speed of 30 s. -1 The mixture was mixed at 100° C. for 5 minutes and passed through an ultrasonic vibration sieve with a mesh size of 54 μm to obtain Toner 1. The physical properties of Toner 1 are shown in Table 3.

[0120] The toner 1 and the magnetic carrier were mixed for 0.5 seconds using a V-type mixer (product name: V-10 type, Tokuju Manufacturing Co., Ltd.) so that the toner concentration was 9% by mass. -1The mixture was mixed for 10 minutes at 30° C. and 5 minutes at 60° C. The magnetic carrier used was magnetic ferrite carrier particles (number average particle size: 35 μm) whose surfaces were coated with an acrylic resin. In this manner, a two-component developer 1 was obtained.

[0121] The evaluation described below was carried out using two-component developer 1. The evaluation results are shown in Table 4.

[0122] [Examples 2 to 12 and Comparative Examples 1 to 2] Toners 2 to 14 were prepared in the same manner as in Example 1, except that the amorphous polyester resin, crystalline polyester resin, and wax were changed as shown in Table 2, and two-component developers 2 to 14 were prepared in the same manner. Furthermore, evaluations were performed in the same manner as in Example 1. The evaluation results are shown in Table 3. The wax used in toners 9 to 11 is a Fischer-Tropsch wax having an endothermic peak temperature of 98°C, and the wax used in toner 12 is a paraffin wax having an endothermic peak temperature of 78°C.

[0123] [Table 2]

[0124] [Table 3]

[0125] [evaluation] A modified Canon Inc. full-color copier (product name: imagePRESS C10000VP) was used as the image forming apparatus, and two-component developer 1 was placed in the cyan station developer, and evaluation was performed in the following manner. The test environment was a high temperature and high humidity environment (30°C / 80% RH).

[0126] <Evaluation 1: Fixation separation property> Paper: CS-068 (68g / m 2 ) (Sold by Canon Marketing Japan Inc.) Toner load on paper: 1.20mg / cm 2(Adjusted by DC voltage VDC of developer carrier, charging voltage VD of electrostatic latent image carrier, and laser power) Evaluation image: A 29cm x 5cm image is placed on the A4 paper with a 3mm margin at the top in the longitudinal direction. Fixing test environment: Temperature 30℃ / Humidity 80%RH (hereinafter referred to as "H / H") Fixing temperature: 120℃ to 170℃ in 1℃ increments Process speed: Set to 321mm / sec The above evaluation image was output, and the fixation separation property was evaluated. Fixation was performed at each fixation temperature, and visual observation was made to see whether wrapping occurred during fixation. The upper limit temperature at which wrapping was not observed was determined as the fixation separation temperature. The fixation separation temperature was evaluated according to the following evaluation criteria.

[0127] (Evaluation Criteria) A: Separation temperature 160℃ or higher B: Separable temperature: 150℃ or higher and less than 160℃ C: Separable temperature: 140℃ or higher and less than 150℃ D: Separable temperature: below 140℃

[0128] <Evaluation 2: Gloss uniformity> The gloss uniformity was evaluated using A3 size paper (product name: CF-C081, basis weight: 81.4 g / m) at the same process speed as in Evaluation 1. 2 Three full-surface solid images (image density 1.55) were printed onto a printer (sold by Canon Marketing Japan Inc.), and the third image was used for evaluation. The gloss level against incident light at 60° was measured using a gloss meter. The gloss of the output image was measured at five points, and the difference between the maximum and minimum values ​​of the five points was judged using the following index. A handheld gloss meter (product name: PG-I; manufactured by Nippon Denshoku Industries Co., Ltd.) was used as the gloss meter.

[0129] (Gloss uniformity evaluation criteria) A: Less than 2.0% B: 2.0% or more and less than 3.5% C: 3.5% or more and less than 5.0% D: 5.0% or more

[0130]

Table 4

Claims

1. A toner comprising toner particles containing an amorphous polyester resin, a crystalline polyester resin, and a hydrocarbon wax, the crystalline polyester resin is a condensation polymer of 1,12-dodecanediol and sebacic acid; The toner exhibited the following properties when measured by differential scanning calorimetry (DSC): I: Heating from 20° C. to 180° C. at a heating rate of 10° C. / min II: After step I, a step of cooling to 20° C. at a temperature drop rate of 10° C. / min. When the measurement is performed in the above manner, the peak temperature (°C) of the peak derived from the wax observed in step II is T2w, the heat generation amount (J / g) is H2w, the peak temperature (°C) derived from the crystalline polyester resin is T2c, and the heat generation amount (J / g) is H2c, which satisfies the following relationship: 9≦T2w-T2c≦15 2.1≦H2w / H2c≦3.8

2. 2. The toner of claim 1, wherein said hydrocarbon wax is a Fischer-Tropsch wax.

Citation Information

Patent Citations

  • Electrostatic charge image developing toner and method for manufacturing the same, electrostatic charge image developer, and image forming method

    JP2007086502A

  • Toner for electrostatic charge image development, electrostatic charge image developer, toner cartridge, process cartridge, and image forming apparatus

    JP2009210913A

  • Toner

    JP2017003915A

  • toner

    JP2017107167A

  • Manufacturing method of toner

    JP2017107170A